1996
DOI: 10.1021/jp953355r
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Deactivation of CDCl3 Excited with a TEA CO2 Laser

Abstract: The decay of infrared fluorescence from IR multiphoton excited CDCl 3 was studied as a function of incident fluence and pressure of added Ar. The decays were exponential and allowed for the calculation of the average energy transferred per collision, 〈〈∆E〉〉, with Ar and with CDCl 3 , as a function of the average internal energy of excited CDCl 3 using a direct method. Identical information was obtained following the inversion procedure developed by Barker et al. (Int. ReV. Phys. Chem. 1993, 12, 2, 305). Both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A master rate equation is presented in Sec. 3 in line with the general formulation used in energy transfer studies [18] together with some representative computations to illustrate the behaviour of economic systems evolving to the equilibrium distribution.…”
Section: Introductionmentioning
confidence: 99%
“…A master rate equation is presented in Sec. 3 in line with the general formulation used in energy transfer studies [18] together with some representative computations to illustrate the behaviour of economic systems evolving to the equilibrium distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the laser pulse length is about 200 ns, at a collisional frequency of 1 × 10 8 s -1 the parent molecules suffer about 20 gas kinetics collisions during the process of excitation. Modeling calculations performed for molecules of similar type showed that the absorption process occurs in the first 200 ns and that it is not affected by energy transfer to Ar during the laser pulse . In the present case, from the experimental relaxation rates it can be deduced that at t = 200 ns, the energy has fallen, at most, to 0.93 its initial value, even in the most favorable experimental conditions for vibrational relaxation used (0.7 Torr of ClFCCFCl and 27 Torr of Ar).…”
Section: Resultsmentioning
confidence: 47%
“…Modeling calculations performed for molecules of similar type showed that the absorption process occurs in the first 200 ns and that it is not affected by energy transfer to Ar during the laser pulse. 16 In the present case, from the experimental relaxation rates it can be deduced that at t ) 200 ns, the energy has fallen, at most, to 0.93 its initial value, even in the most favorable experimental conditions for vibrational relaxation used (0.7 Torr of ClFCdCFCl and 27 Torr of Ar). Thus we conclude that the measured value of 〈n〉 is not seriously affected by the relaxation process.…”
Section: Combining Eqs 3 and 5 Results Inmentioning
confidence: 49%
“…IRF has generally been used with cyclic ring systems, usually aromatics, excited by internal conversion (IC) following visible/UV excitation (hereafter referred to as IC-IRF), as has UV absorption spectroscopy (hereafter referred to as IC-UVA). There have been very few studies using the combination of IRMPA coupled with time-resolved IRF (hereafter referred to as IRMPA-IRF). ,, …”
Section: Introductionmentioning
confidence: 99%